(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
SnO_2 hydrosol made in the lab was deposited on HTPET fibers by dip-coating method. In order to improve the deposition of the coating layer and water adsorption properties of the fiber, atmospheric plasma treatment was used as pre-treatment to enhance the interaction at the interface. Photocatalytic properties of the samples coated with SnO_2 under different plasma treatments were analyzed through the degradation of methylene blue under UV-light. The morphologies and surface modulus of SnO_2 coated fibers were characterized by Scanning Electronic Microscope (SEM) and Atomic Force Microscopy (AFM), respectively. The effects of plasma treatment on water adsorption behavior of the fibers were examined by contact angle measurement instrument. Tensile tests were carried out to measure and assess the mechanical properties of HTPET fiber before and after plasma treatment and photocatalysis was done. The study revealed that the photocatalytic activity of SnO_2 coated HTPET fibers were enhanced due to the wettability of HTPET surfaces improved by plasma treatment and varying degrees of surface etching which benefited SnO_2 adhesion on HTPET fibers. Meanwhile, the modulus of monofilament surface increased under plasma treatment but decreased after phtotcatalysis. Mechanical properties of the fibers exhibited an opposite trend. It was found that the best photocatalytic activity of HTPET fibre was obtained under 100 w power plasma treatment.